A new species of Lachesilla in the pedicularia group and new records of Psocoptera (Insecta: Psocodea) from Paraguay - Alfonso N. García-Aldrete (Revista Mexicana de Biodiversidad, 2014)
A new species of Lachesilla in the pedicularia group is here described and illustrated. It belongs in an assemblage of species occurring in South America and southern Mexico. The types are deposited in the National Insect Collection(CNIN), Instituto de Biología, UNAM. Records of 9 species of Psocoptera, in 4 genera previously unknown in Paraguay are presented.